2020
DOI: 10.1055/a-0998-3708
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of endoscopic resection for superficial non-ampullary duodenal tumors

Abstract: Background and study aims Because superficial non-ampullary duodenal epithelial tumors (SNADETs) are relatively rare, studies evaluating the outcomes of endoscopic resection (ER) for SNADETs are limited. Therefore, this study aimed to evaluate the clinical validity of ER for SNADETs. Patients and methods The study participants included 163 consecutive patients (108 men; mean age, 61.5 ± 11.3 years) with 171 SNADETs, excluding patients with familial adenomatous polyposis resected by ER, at Hiroshima U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
0
24
1
Order By: Relevance
“…ESD is reported to accomplish secure en bloc resection for superficial epithelial tumors arising from the gastrointestinal tract irrespective of the size and location [11][12][13][14] . Similarly, duodenal ESD accomplishes higher en bloc resection rates in previous reports [15][16][17][18][19][20][21][22] . Moreover, a recent multicenter retrospective study including more than 3000 cases undergoing duodenal endoscopic treatment in Japan reported high duodenal ESD en bloc resection rates regardless of the size, location, or presence of fibrosis of the lesion, whereas other endoscopic resection techniques including endocopic mucosal resection (EMR) and underwater EMR revealed inferior resectability, especially for lesions larger than 20 mm [23] .…”
Section: Indications For Esd and Cure Criteriamentioning
confidence: 57%
“…ESD is reported to accomplish secure en bloc resection for superficial epithelial tumors arising from the gastrointestinal tract irrespective of the size and location [11][12][13][14] . Similarly, duodenal ESD accomplishes higher en bloc resection rates in previous reports [15][16][17][18][19][20][21][22] . Moreover, a recent multicenter retrospective study including more than 3000 cases undergoing duodenal endoscopic treatment in Japan reported high duodenal ESD en bloc resection rates regardless of the size, location, or presence of fibrosis of the lesion, whereas other endoscopic resection techniques including endocopic mucosal resection (EMR) and underwater EMR revealed inferior resectability, especially for lesions larger than 20 mm [23] .…”
Section: Indications For Esd and Cure Criteriamentioning
confidence: 57%
“…The macroscopic presentation for sporadic duodenal adenoma is mainly milk-white or reddish mucosa (▶ Fig. 1) [16,17], and the morphology of the lesion is usually 0-IIa in the Paris classification [17][18][19]. The associations between the macroscopic type or the tumor size and malignancy have been analyzed with conflicting results [1,13,20,21].…”
Section: Endoscopic Assessment Biopsy and Stagingmentioning
confidence: 99%
“…In more recent retrospective studies, high rates of complete endoscopic resection (90.5 %-96.1 %) have been obtained with EMR, whereas the adverse event rates ranged from 2 % to 24.4 % [17,19,[53][54][55][56][57][58][59][60][61]. Increasing lesion size was associated with reduced rates of en bloc resection as well as increased rate of adverse events [50,53,[55][56][57]62].…”
Section: Duodenal Emr In Management Of Large Adenomasmentioning
confidence: 99%
“…Similarly, in the duodenum, ESD has been reported to achieve a high en bloc resection rate, regardless of the size of the lesion. 17 , 19 , 22 , 23 , 24 , 25 , 31 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 Secure local resectability is one of the greatest advantages of ESD for reducing local residual recurrence. In fact, it has been reported that local recurrence occurs up to 30% of large lesions in the duodenum when the resection results in piecemeal resection 22 , 24 , 58 , 59 , 60 , 61 , 62 (Table 3 ).…”
Section: Endoscopic Submucosal Dissectionmentioning
confidence: 99%